Жангалина Э.Д., Жұмабаева Б.Ә., Айташева З.Ғ., Лебедева Л.П., Шыңғысқызы Н. Селекция мен тағамдық өндірісте көкөністік үрмебұршақты пайдалану перспективалары: Казахский национальный университет им. аль-Фараби, Казахстан, г. Алматы, *e-mail: Erika.Dzhangalina@kaznu.kz (Eurasian Journal of Ecology, 2018)
Prospects for using vegetable beans for breeding and food productionOne of the most prospective strategies of agricultural policy in the Republic of Kazakhstan at presentis manufacturing effective competitive agricultural production and supply with quality food products.Major role in this direction belongs to growing sowing areas of legumes, and common in particular.Common bean is one of basic vegetable crops of high economic value in different countries. Out ofall legumes common bean has high nutritional value and may be used for different nutritional aims. Inhuman daily ration in many countries common bean is the resource of proteins, essential and non-essential amino-acids, micro and macro elements and vitamins. In modern world the breeding of vegetablebean should be targeted to generation of new, prospective varieties on the basis of complex assessmentof domestic and foreign genotypes by implying marker selection and introduction new technologies. Main biological and morphological characteristics of vegetable beans, i.e. agronomical and foodvalues, are highlighted in this article. There are the key principles and modern research in the field of thelegumes breeding which are accepted in different countries. Analysis of literature sources of Russian andforeign authors over the past 10-15 years has demonstrated that breeding of vegetable beans should beconcentrated on complex assessment of specimens in accord with such traits as productivity, resistanceto stress factors and increased nutritional value.To assess productivity it is necessary to take into account that the modern varieties of common beanshave high biological and physiological difference across populations, i.e. the presence of biotypes withlow, medium and high potential of the traits. One of the ways towards increased productivity is providing experiments on optimizing biotic structure of populations.Currently these investigations are conducted by conventional and molecular genetic methods. Introduction of marker selection on the basis of DNA-markers will promote the development of new,prospective varieties with economically valuable characteristics and disease resistance for agriculturalharvesting.This article provides main directions of the use of marker selection to determine specimens and varieties which are resistant to drought, viral and fungal diseases, the study and the assessment of geneticdiversity of common bean genotypes.Principal investigations on cultivation of varieties with increased nutritional value is aimed at improving quality and quantity composition of proteins, balanced in amino acids, enriched with microelements and vitamins and possessing low amount of antinutrients. These varieties will allow to meet theneeds of food industry in legumes and make vegetable beans more widespread. Special attention is paidto the prospects of cultivation of vegetable beans in Kazakhstan. It has been shown, that the expansion ofcultivation areas is quite profitable having high economic importance for our Republic. The introductionof the beans into agricultural production will assist in increasing the profitability of the farms, to developnew branches of food industry, provide plant products with high protein content of the to the populationof our Republic and improve people,s health and wealth.Key words: vegetable beans, cultivar, breeding, food industry.